Export Stagnation and Autarkic Development in Brazil, 1947-1962 - Leff, Nathaniel H. (Quarterly Journal of Economics, 1967)
I. Data on export stagnation, 286. — II. Causes of export stagnation. 287. — III. Effects of export stagnation, 292. — IV. Possibilities for change, 296. — V. Conclusions, 299.